2015
DOI: 10.1016/j.bbadis.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in APP and CP mRNA expression supports impairment of iron export in Alzheimer's disease patients

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder of still unknown etiology and the leading cause of dementia worldwide. Besides its main neuropathological hallmarks, a dysfunctional homeostasis of transition metals has been reported to play a pivotal role in the pathogenesis of this disease. Dysregulation of iron (Fe) metabolism in AD has been suggested, particularly at the level of cellular iron efflux. Herein, we intended to further clarify the molecular mechanisms underlying Fe homeostasis in AD. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…[43] This sequence was confirmed by recent studies showing Tf desaturation [49] and downregulation of ceruloplasmin and APP in the plasma of AD patients, [50] observations consistent with impaired iron export. Thus, iron accumulation appears to be an effect of AD progression.…”
Section: Are Changes In Brain Iron Homeostasis a Cause Or Effect Osupporting
confidence: 65%
“…[43] This sequence was confirmed by recent studies showing Tf desaturation [49] and downregulation of ceruloplasmin and APP in the plasma of AD patients, [50] observations consistent with impaired iron export. Thus, iron accumulation appears to be an effect of AD progression.…”
Section: Are Changes In Brain Iron Homeostasis a Cause Or Effect Osupporting
confidence: 65%
“…Recently, another study showed significantly the decreased expression of aconitase 1 (ACO1), CP, and APP in peripheral blood mononuclear cells in AD patients as compared to controls, pointing to a down‐regulation of cellular iron export in AD over control (Guerreiro et al . ).…”
Section: Altered Iron Homeostasis In Neurodegenerative Diseasesmentioning
confidence: 97%
“…Recently, application of specialized techniques such as size exclusion chromatography-inductively coupled plasma-mass spectrometry (SEC-ICP-MS), which enables measurement of iron saturation of proteins such as ferritin or transferrin rather than measurement of total protein levels (Hare et al 2013b), revealed significantly decreased plasma iron in AD patients (Faux et al 2014) because of transferrin desaturation (Hare et al 2015b). Recently, another study showed significantly the decreased expression of aconitase 1 (ACO1), CP, and APP in peripheral blood mononuclear cells in AD patients as compared to controls, pointing to a down-regulation of cellular iron export in AD over control (Guerreiro et al 2015).…”
Section: Involvement Of Iron In Ad Pathologymentioning
confidence: 99%
“…parietal cortex, motor cortex, and hippocampus (Bartzokis et al, 1994, Bartzokis and Tishler, 2000, Ding et al, 2009, Pfefferbaum et al, 2009, Bilgic et al, 2012, Luo et al, 2013, Langkammer et al, 2014, Tao et al, 2014, Ghadery et al, 2015. Systemic changes in iron homeostasis accompany AD such as decreased iron in plasma, resulting from Tf desaturation, and decreased cellular iron export indicated by decreased expression of aconitase 1, Cp and APP in peripheral blood mononuclear cells of AD patients vs. normal subjects (Faux et al, 2014, Guerreiro et al, 2015, Hare et al, 2013, Hare et al, 2015. Several studies implicate iron in the aggregation, oligomerisation, amyloidosis, and toxicity of Aβ peptides (Mantyh et al, 1993, Schubert and Chevion, 1995, Huang et al, 2004b, Liu et al, 2011.…”
Section: Role Of Iron In Neurodegenerationmentioning
confidence: 99%